In Vivo Evaluation of Selective Carbonic Anhydrase Inhibitors as Potential Anticonvulsant Agents. (24th February 2016) - Bruno, Elvira; Buemi, Maria R.; De Luca, Laura; Ferro, Stefania; Monforte, Anna‐Maria; Supuran, Claudiu T.; Vullo, Daniela; De Sarro, Giovambattista; Russo, Emilio; Gitto, Rosaria
Abstract: Epilepsy is a common neurological disorder caused by an imbalance between inhibitory and excitatory neurotransmission. It is well known that neuronal excitability is related to γ‐aminobutyric acid (GABA)ergic depolarization. HCO3 − ‐dependent depolarization can be suppressed by membrane‐permeable inhibitors of carbonic anhydrase. We previously identified some isoquinoline sulfonamides as potent and selective inhibitors of the human carbonic anhydrase II and VII (hCA II and hCA VII) isoforms. Given that hCA II and hCA VII are specific isoforms involved in GABA‐mediated neuronal excitation, we hypothesized that they could represent the biological target for the development of new anticonvulsant agents. Therefore, for selected isoquinoline sulfonamides, we preliminarily tested their ability to prevent audiogenic seizures in DBA/2 mice. All compounds were evaluated after intraperitoneal administration, and some of them proved to protect the mice against convulsions. Among this series of compounds, several derivatives showed combined in vivo efficacy with inhibitory effects toward the targeted carbonic anhydrases (i.e., hCA II and hCA VII). Specifically, the most interesting molecule was 1‐(4‐aminophenyl)‐6, 7‐dimethoxy‐3, 4‐dihydroisoquinoline‐2(1 H )‐sulfonamide (6 ), which proved to be a more active and selective hCA VII inhibitor than the reference compound topiramate. Further studies to explore the in vivo pharmacokinetic profile of the most active compounds may help to provide insight into the future design of selective hCA VII inhibitors. Abstract : Something on the brain : We evaluated the anticonvulsant effects of sulfonamide derivatives showing high selectivity toward the human carbonic anhydrase VII isoform. The most active compound is a potentially useful lead structure for further development of anticonvulsants.